2021
DOI: 10.1159/000515032
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of <b><i>Morus nigra</i></b> and Its Phytochemicals against Hepatotoxicity: A Review of Preclinical Studies

Abstract: <b><i>Background:</i></b> Our liver has a variety of vital functions including removing poisons, storing energy, immunological roles, and secretory and excretory functions. It may face some kinds of diseases caused by viruses, hepatotoxic chemicals, drugs, alcohol, and inherited disorders. Oxidative stress and inflammation are in the core of mechanisms of liver damages induced by viruses or chemical agents. <b><i>Summary:</i></b> <i>Morus nigra</i> (&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Phytochemicals derived from plants, such as flavonoids, terpenoids, phenolics, alkaloids, and other compounds, are recognized for their potential to confer numerous benefits to the body, particularly in supporting liver function. [19][20] Key effects include minimizing liver damage, detoxification, and safeguarding the liver against harmful agents. Within black shallot extract, the presence of polyphenols and flavonoids allows for intricate interactions with other phytochemicals, creating a synergistic collaboration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemicals derived from plants, such as flavonoids, terpenoids, phenolics, alkaloids, and other compounds, are recognized for their potential to confer numerous benefits to the body, particularly in supporting liver function. [19][20] Key effects include minimizing liver damage, detoxification, and safeguarding the liver against harmful agents. Within black shallot extract, the presence of polyphenols and flavonoids allows for intricate interactions with other phytochemicals, creating a synergistic collaboration.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of these compounds not only targets the liver but also contributes to overall health benefits for the body. 19 Consequently, black shallot extract not only provides essential phytochemicals but also stimulates positive interactions among them, effectively protecting the liver and sustaining its functionality.…”
Section: Resultsmentioning
confidence: 99%
“…Blackberry phenolic compounds have demonstrated the capacity to diminish LDL oxidation, quench free radicals by hydrogen molecule donation, and interfere with liposome oxidation systems [165,166]. In particular, anthocyanins from M. nigra showed the capacity to protect human primary endothelial cells by decreasing the production of the cytokine-induced chemokine monocyte chemotactic protein 1, a protein directly linked to atherogenesis, and which is mainly responsible for attracting macrophages to sites of infection or inflammation [167].…”
Section: Cardiovascular Protectionmentioning
confidence: 99%
“…In epidemiological studies, diets high in plant-derived phenolic compounds have been shown to reduce the incidence of coronary heart disease. The chronic antioxidant and hypolipidemic characteristics of these compounds play critical roles in the prevention of lipoprotein oxidation and the formation of atherosclerotic lesions [2,122,166,169].…”
Section: Cardiovascular Protectionmentioning
confidence: 99%
“…Many research studies reported the phytochemical and pharmacological aspects of M. nigra as an antidiabetic drug [103,113,141] and found that all botanical parts (leaves, root, branches and fruits) have special effects on antidiabetic activity [26,72,113,142].…”
Section: Antidiabetic Therapymentioning
confidence: 99%